Impact assessment of rural electrification through photovoltaic kits on household expenditures and income: The case of Morocco - Abdellah Oulakhmis; Rachid Hasnaoui; Youness Boudrik (Economies, 2025)
This study evaluates the socio-economic impact of rural electrification through photovoltaic (PV) systems in Morocco. As part of the country's broader energy transition strategy, decentralized renewable energy solutions like PV kits have been deployed to improve energy access in isolated rural areas. Using quasi-experimental econometric techniques, specifically propensity score matching (PSM) and estimation of the Average Treatment Effect on the Treated (ATT), the study measures changes in household income, expenditures, and economic activities resulting from PV electrification. The results indicate significant positive effects on household income, electricity spending, and productivity in agriculture and livestock. These findings highlight the critical role of decentralized renewable energy in advancing rural development and poverty reduction. Policy recommendations include expanding PV access with complementary support measures such as microfinance and technical training.
Keywords: 330; Morocco; photovoltaic systems; renewable energy; rural electrification; socio-economic impact